DOES FINANCIAL LITERACY AND INCLUSION AFFECT VILLAGE OWNED ENTERPRISES FINANCIAL PERFORMANCE - Nur Aisyah Kustiani; Sriyani; Arifah Fibri Andriani (Halu Oleo University, 2023)
This study aims to examine the impact of financial literacy and financial inclusion on financial performance with rational decision-making and financial capital as mediating variables. This study uses a partial least square structural equation model since this study uses latent variables. All variables in this study were measured using a questionnaire distributed to BUM Desa managers in East Jawa Province using a convenience sampling technique. A total of 69 questionnaires were returned and used in this study. The financial literacy of BUM Desa managers has a direct influence on improving BUMDesa's financial performance. Financial inclusion of BUM Desa will motivate BUM Desa managers to be rational in making capital decisions that will affect the improvement of financial performance. This study cannot prove the effect of financial inclusion on financial performance. This study failed to prove the mediating role of the impact of financial literacy on financial performance.